Information Frictions and the Law of One Price: "When the States and the Kingdom became United" - Claudia Steinwender (Oesterreichische Nationalbank (OeNB), 2014)
How do information frictions distort international trade? This paper exploits a unique historical experiment to estimate the magnitude of these distortions: the establishment of the transatlantic telegraph connection in 1866. I use a newly collected data set based on historical newspaper records that provides daily data on information flows across the Atlantic together with detailed, daily information on prices and trade flows of cotton. Information frictions result in large and volatile deviations from the Law of One Price. What is more, the elimination of information frictions has real effects: Exports respond to information about foreign demand shocks. Average trade flows increase after the telegraph and become more volatile, providing a more efficient response to demand shocks. I build a model of international trade that can explain the empirical evidence. In the model, exporters use the latest news about a foreign market to forecast expected selling prices when their exports arrive at the destination. Their forecast error is smaller and less volatile the more recent the available information. I estimate the welfare gains from information transmission through the telegraph to be roughly equivalent to those from abolishing a 6% ad valorem tariff.
Keywords: 330; Außenhandel; Informationsverbreitung; Handelseffekt; Preiskonvergenz; Großbritannien